Perencanaan Strategis TI pada BMKG Palembang Menggunakan Metode Ward and Peppard - Kenny Lie; Dicky Pratama (BETRIK, 2025)
This study designs a strategic planning for Information Systems and Information Technology (IS/IT) to improve IT infrastructure optimization at the Sultan Mahmud Badaruddin II Meteorological Station in Palembang using the Ward & Peppard framework. Internal and external environmental analysis is conducted through Value Chain, SWOT, McFarlan Strategic Grid, PEST, and identification of critical success factors to generate an application portfolio and prioritize IT initiatives. The findings indicate that BMKG SMB II has quite robust observation tools, such as radar and automatic weather stations, but still faces challenges in data integration, digitalization of observation processes, IT human resource capacity, and network limitations, especially in frontier, outermost, and disadvantaged areas. Strategic recommendations include the development of an integrated data and analytics platform with an AI-based quality control mechanism, automation of information collection, validation, and dissemination processes, strengthening cybersecurity and infrastructure resilience through IoT-based predictive maintenance, and improving human resource competencies. The 2025–2029 Roadmap prioritizes strengthening security, data integration, and human resource development before the gradual implementation of advanced technologies through pilots, evaluations, and expansions to support improved public service quality.